2017
DOI: 10.1101/186007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inter-areal balanced amplification enhances signal propagation in a large-scale circuit model of the primate cortex

Abstract: Reliable signal transmission represents a fundamental challenge for cortical systems, which display a wide range of weights of feedforward and feedback connections among heterogeneous areas. We re-examine the question of signal transmission across the cortex in network models based on recently available mesoscopic, directed-and weighted-inter-areal connectivity data of the macaque cortex. Our findings reveal that, in contrast to feed-forward propagation models, the presence of long-range excitatory feedback pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 61 publications
3
65
0
Order By: Relevance
“…We found that the population transfer function approximated a sigmoid activation function ( Figure 5B). Approximating the mean-field transfer function of a cortical area allowed us to focus our modeling efforts on simplified excitatory networks across large cortical areas, since most inter-area cortical networks rely on excitatory connectivity (Joglekar et al, 2018) . The population spike rate (excitatory cells only) subject to inhibitory regulation.…”
Section: From Neurons To Neural Masses: Modeling Neural Dynamics Of Cmentioning
confidence: 99%
“…We found that the population transfer function approximated a sigmoid activation function ( Figure 5B). Approximating the mean-field transfer function of a cortical area allowed us to focus our modeling efforts on simplified excitatory networks across large cortical areas, since most inter-area cortical networks rely on excitatory connectivity (Joglekar et al, 2018) . The population spike rate (excitatory cells only) subject to inhibitory regulation.…”
Section: From Neurons To Neural Masses: Modeling Neural Dynamics Of Cmentioning
confidence: 99%
“…1b) (Wang, 2001;Wong and Wang, 2006). In addition, there is a macroscopic gradient of synaptic excitation (Chaudhuri et al, 2015;Joglekar et al, 2018; Extended Data Fig. 2), namely the number of spines, loci of excitatory synapses, per pyramidal cell (Elston 2007) was used as a proxy for the strength of recurrent and long-range excitation that increases along the cortical hierarchy (Felleman and van Essen, 1991;Markov et al, 2014; Fig.…”
mentioning
confidence: 99%
“…The variants were constrained by a plethora of experimental data: the representation of the individual cells and their firing behavior in response to somatic current injections, LGN filters, thalamocortical connectivity, recurrent connectivity, and activity patterns observed in vivo. This work continues the trend of developing increasingly more sophisticated models of cortical circuits in general (e.g., Traub et al, 2005;Zhu, Shelley and Shapley, 2009;Potjans and Diesmann, 2014;Markram et al, 2015;Joglekar et al, 2018;Schmidt et al, 2018) and visual cortex in particular (Wehmeier et al, 1989;Troyer et al, 1998;Zemel and Sejnowski, 1998;Krukowski and Miller, 2001;Arkhipov et al, 2018;Antolík et al, 2019). Our main goal was to integrate existing and, especially, emerging multi-modal experimental datasets describing the structure and in vivo activity of cortical circuits into biologically realistic network models.…”
Section: Simulating the Models Using Diverse Stimulimentioning
confidence: 76%
“…Simulating cortical circuits has a long history (e.g. (Wehmeier et al, 1989;Zemel and Sejnowski, 1998;Troyer et al, 1998;Krukowski and Miller, 2001;Traub et al, 2005;Zhu, Shelley and Shapley, 2009;Potjans and Diesmann, 2014;Markram et al, 2015;Arkhipov et al, 2018;Joglekar et al, 2018;Schmidt et al, 2018;Antolík et al, 2019;Schwalger and Chizhov, 2019)), with models incrementally building upon their predecessors. The simulations described here are a further instance of this evolution toward digital simulacra that predict new experiments, are insightful, and ever more faithful to the vast complexity of cortical tissue, in particular its heterogeneous neuronal cell classes, connections, and in vivo activity.…”
Section: Introductionmentioning
confidence: 99%